2009
DOI: 10.1515/hc.2009.15.5.323
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Synthesis Of 3-Amino B-Lactams Derived From Polyaromatic Compounds

Abstract: A simple an effective method for the synthesis of a few trans 3-amino ß-lactams derived from polyaromatic compounds has been accomplished via the deprotection of phthalimido groups with ethylene diamine.Ar,= Ar,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The 3-amino substituted b-lactams were synthesized following the procedure developed in our laboratory. 49,50 The reaction proceeded equally well irrespective of the nature of substituent present in the b-lactam ring without any change of stereochemistry. A series of diversely C,N-disubstituted 3-amino b-lactams yielded the corresponding N-(2-azetidinoyl)-2,5-dimethyl pyrroles following Scheme 2.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The 3-amino substituted b-lactams were synthesized following the procedure developed in our laboratory. 49,50 The reaction proceeded equally well irrespective of the nature of substituent present in the b-lactam ring without any change of stereochemistry. A series of diversely C,N-disubstituted 3-amino b-lactams yielded the corresponding N-(2-azetidinoyl)-2,5-dimethyl pyrroles following Scheme 2.…”
Section: Resultsmentioning
confidence: 90%
“…We have demonstrated the catalytic activity of trivalent bismuth nitrate pentahydrate in a number of examples. These investigations resulted in various novel methods that include nitration of aromatic systems, [27][28][29] Michael reaction, 30 protection of carbonyl compounds, 31 deprotection of oximes and hydrazones, 32 Paal-Knorr synthesis of pyrroles, 33 hydrolysis of amide, 34 electrophilic substitution of indoles, 35,36 synthesis of a-aminophosphonates, 37 and Hantzsch 1,4-dihydropyridines 38 . Our success in the bismuth nitrate-induced reaction has revealed that this reagent acts as a Lewis acid type of activator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the cases, the reactions are completed within 1–3 min and the products are obtained in excellent yield ( Table 3 ). The 3-amino-2-azetidinones were synthesized following the procedure published from our laboratory [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…After completion of the reaction, the reaction mixture was washed with brine and water successively. The organic layer was dried over anhydrous sodium sulfate and the 3-amino β-lactam was isolated in pure form by column chromatography over neutral alumina (methanolic ethyl acetate) in good yield [ 33 ]. The stereochemistry of β-lactams remains unchanged during this conversation.…”
Section: Methodsmentioning
confidence: 99%